Strategic direction setting of DFIS: A qualitative review based on performance model - Shamsudin, Norazidah; Mhd. Sarif, Suhaimi; Mohammed, Mustafa Omar; Mustaffa Kamil, Nazrol Kamil (Allied Academies, 2018)
DFIs are specialized financial institution, appointed by the government and been entrusted for specific mandated roles on socio-economic development. In Malaysia, the mandate of DFIs is merely similar to Islamic economic objective that is for society benefit. Hence, the study been carried out to analyze on the Islamic economic objectives coverage by the DFIs and to explore on the involvement of the Shari’ah committee member of DFIs in the direction setting of the institution. All six Malaysian DFIs which prescribed under DFIA 2002 been included in the study. The result from content analysis shows that there is one Maqasid dimension which not been covered in the DFIs’ vision and mission statement. Furthermore, there is none DFI covers all nine PMMS model’s dimensions as the most covered is six dimensions. Based on interviews, it is found that the Shari’ah committee member is not involved directly in the direction setting of the institution but rather involved in the supervision and assisting the DFIs in Shari’ah matters. It is recommended the DFIs to shape their direction towards fulfilling the Islamic economic objectives since they are mandated so besides their intent to be as full-fledged Islamic. In ensuring the truthful attainment of Islamic economic objective, it is also suggested the Shari’ah committee member to be included as they could contribute on Maqasid Shari’ah perspective in determining and shaping the strategic direction of the institution.